Exploring the impact and challenges of digital currency: the literature review / Suzana Muhamad Said...[et al.] - Muhamad Said, Suzana; Abdul-Majid, Mariani; Said, Fathin Faizah (2018)
This article explores the literature review as an effort to examine the relevant studies on the impact and challenges of digital currency based on selective economics and legal issues. The scope of research is generally on the issues arising from the impact and challenges of digital currency. The methodology used is socio-legal analysis with reference to text materials and examples. The expected outcome will enable some insights on the impact and challenges concerning digital currency for application in Malaysia